Vaccine-Related Encephalopathy Rediagnosed as Dravet Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Five patients with a history of seizures in the first year of life, occurring within 24 hours of DPT vaccination, were subsequently tested positive for SCN1A, and with support of genetic testing were diagnosed with Dravet syndrome, in a report from San Antonio Military Medical Center; Northwestern University School of Medicine, Children's Memorial Epilepsy Center, Chicago; Baylor College of Medicine, and Texas Children's Hospital, Houston, TX.